2012
DOI: 10.1021/jp209832h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-Mercaptoethanol on Quantum Dot Emission Evaluated from Photoluminescence Decays

Abstract: β-mercaptoethanol (BME) has been used as an "anti-blinking" reagent with quantum dots (QDs), but its exact effects on the luminescence behavior of different QD materials have not been quantified. In this study, the luminescence lifetime decays of aqueous solutions of CdTe QDs solubilized with mercaptopropionic acid (MPA) are measured by timecorrelated single photon counting (TCSPC) in the presence of varying concentrations of BME. The decays are fit to a model of radiative recombination and trapping that yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…It is found that the fluorescence of the QDs capped either with the amines or thiols when exposed to air is quenched due to slow reaction of the QDs with O 2 . 68,69 As expected, on exposure to air the CdTe/ HDA QDs in CHCl 3 , a blue shift of the absorption and emission maxima and a decrease in the peak amplitude of the absorption and quenching of the fluorescence intensity and lifetime are observed (Figure 5a) with time. The same experiment, when performed with CdTe/SH-UMIM in [bmim][BF 4 ], reveals (Figure 5b) the stability of QD-IL hybrids toward O 2 .…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…It is found that the fluorescence of the QDs capped either with the amines or thiols when exposed to air is quenched due to slow reaction of the QDs with O 2 . 68,69 As expected, on exposure to air the CdTe/ HDA QDs in CHCl 3 , a blue shift of the absorption and emission maxima and a decrease in the peak amplitude of the absorption and quenching of the fluorescence intensity and lifetime are observed (Figure 5a) with time. The same experiment, when performed with CdTe/SH-UMIM in [bmim][BF 4 ], reveals (Figure 5b) the stability of QD-IL hybrids toward O 2 .…”
Section: Methodssupporting
confidence: 76%
“…Literature suggests that thiolbased capping agents may or may not protect the QD surface from oxidation. 69 3-mercaptopropionic acid, for example, does not provide any protection from O 2 , whereas β-mercaptoethanol (BME) due to its antioxidant properties does protect the CdTe QDs from surface oxidation. 69 In CHCl 3 , O 2 has a very good solubility (9.8 mM), 70 and when the QDs are exposed to air, O 2 molecules can easily diffuse through this solvent and the capping agent to destroy the surface of the QDs leaving the metal ions and chalcogenide oxides in the solution.…”
Section: Methodsmentioning
confidence: 99%
“…5,8,14,21,[23][24][25][26][27] In ref. 27, Nadeau et al used the one-state trapping model with three fitting parameters to fit the fluorescence decay spectra of mercaptopropionic acid (MPA) coated CdTe QDs under the influence of b-mercaptoethanol (BME), while the fitted data did not display clear relationships with the changes (pH value and BME concentration) in the QD solutions (note that the stretched model and two-exponential model were also used for comparison). It was reported recently 4 that F(t) was well described by the standard bi-exponential model…”
Section: Introductionmentioning
confidence: 99%
“…This type of curve has been seen in many different nanoparticle systems, and for QDs, a few theoretical and experimental studies have associated increased power-law bending with reduced blinking. 28,29,37 This study used a simple one-state trapping model, previously described by us and others, 15,28,29 to fit CdSe and InP QD PL decays to a model containing three parameters: a ''radiative recombination lifetime'' t R , a ''trapping rate'' t m 0 /t e , and a ''blinking parameter'' m. The primary goal of this study was to relate the long-term power law bending of the decay curves to the parameter m, and to determine when a simple power-law fit to the data yielded this parameter. Although the exact correspondence between m and blinking probabilities was not determined in previous studies, m was expected to be related to the off-times rather than the on-times, as it results from a distribution of dwell times in a dark state.…”
Section: Discussionmentioning
confidence: 99%
“…It adheres to QDs via its thiol group (or, at higher pH, its thiolate) and has a redox level well above the valence band edge of CdSe, very close to that of CdTe, and just below that of InP. 14 While we have previously seen that BME can trap holes from CdTe, 15 the slight difference in InP band edge energy as well as the ZnS shell may prevent this occurring with these QDs. The presence of a shell can affect the degree of hole trapping by requiring tunneling through the shell for an interaction to take place.…”
Section: Introductionmentioning
confidence: 99%